Genetic characterization of kushum horses in kazakhstan based on haplotypes of mtdna and y chromosome, and genes associated with important traits of the horses - Nguyen, T. B.; Paul, R. C.; Okuda, Y.; Le, T. N. A.; Pham, P. T. K.; Kaissar, K. J.; Kazhmurat, A.; Bibigul, S.; Bakhtin, M.; Kazymbet, P.; Maratbek, S. Z.; Meldebekov, A.; et al. (Journal of Equine Science. - 2020, 2020)
The Kushum is a relatively new breed of horses in Kazakhstan that was established in the middle of the 20th century through a cross between mares of Kazakhstan local horses and stallions of Thoroughbred, Trotter, and Russian Don breeds to supply military horses. To reveal the genetic characteristics of this breed, we investigated haplotypes of mitochondrial DNA (mtDNA) and single-nucleotide polymorphisms of the Y chromosome, as well as genotypes of five functional genes associated with coat color, body composition, and locomotion traits. We detected 10 mtDNA haplotypes that fell into 8 of the 17 major haplogroups of horse mtDNA, indicating a unique haplotype composition with high genetic diversity. We also found two Y-chromosomal haplotypes in Kushum horses, which likely originated from Trotter and/or Don breeds. The findings regarding the mtDNA and Y-chromosomal haplotypes are concordant with the documented maternal and paternal origins of the Kushum horses. The allele frequencies of ASIP, MC1R, and MATP associated with coat color were consistent with the coat color variations of Kushum horses. The allele frequencies of MSTN associated with endurance performance and those of DMRT3 associated with gait suggested that the observed allele frequencies of these genes were the result of selective breeding for these traits. As a result of this study, we were able to obtain useful information for a better understanding of the origin and breeding history of the Kushum horse breed using molecular markers. Кушум - относительно новая порода лошадей в Казахстане, выведенная в середине 20 века в результате скрещивания кобыл местных казахстанских лошадей и жеребцов чистокровной, рысистой и русской донской пород для снабжения военных лошадей. Чтобы выявить генетические характеристики этой породы, мы исследовали гаплотипы митохондриальной ДНК (мтДНК) и однонуклеотидные полиморфизмы Y-хромосомы, а также генотипы пяти функциональных генов, связанных с окрасом шерсти, составом тела и особенностями передвижения. Мы обнаружили 10 гаплотипов мтДНК, которые попали в 8 из 17 основных гаплогрупп мтДНК лошади, что указывает на уникальный состав гаплотипов с высоким генетическим разнообразием. Мы также обнаружили два гаплотипа Y-хромосомы у кушумских лошадей, которые, вероятно, произошли от пород рысак и / или дон. Результаты, касающиеся мтДНК и гаплотипов Y-хромосомы, согласуются с документально подтвержденным происхождением кушумских лошадей по материнскому и отцовскому признакам. Частоты аллелей ASIP, MC1R и MATP, связанные с окрасом шерсти, соответствовали вариациям окраса шерсти кушумских лошадей. Частоты аллелей MSTN, связанные с выносливостью, и частоты DMRT3, связанные с походкой, предполагают, что наблюдаемые частоты аллелей этих генов были результатом селективного скрещивания по этим признакам. В результате этого исследования мы смогли получить полезную информацию для лучшего понимания происхождения и истории разведения кушумской породы лошадей с использованием молекулярных маркеров.
Keywords: импакт-фактор 2020; научный журнал; зарубежное издание; дальнее зарубежье; коневодство; кушумская порода лошадей; генетика лошадей; скопус; зарубежные авторы